Disaster Mitigation Through Education: A Holistic Approach for Rural Communities - Rakuasa, Heinrich (Yayasan Perguruan Kampus, 2025)
This research discusses the importance of a holistic approach to disaster mitigation through education for rural communities. Rural communities are vulnerable to natural disasters due to limited resources, inadequate infrastructure, and dependence on the agriculture and fisheries sectors. A holistic approach through training, simulation and active community participation can improve preparedness, reduce risk and recover from disaster impacts effectively and sustainably. This research uses a descriptive qualitative approach with a literature study to analyze the importance of disaster mitigation through education for rural communities. The results show that collaboration between the government, community and private sector in disaster mitigation programs is essential. The implication of this research is the need for an increased holistic approach in disaster mitigation education to improve rural communities' awareness and resilience to natural disasters.